Extending social security protection to the domestic workers in Zimbabwe - Makura, Eleanor (My University, 2018)
Domestic workers in Zimbabwe do not belong to any social security system for protection against any shocks such as old age, death, invalidity, illness, maternity or occupational injuries. It is because of these social problems that this research study was carried out. The study seeks to understand the risks domestic workers in the Greenside and Chikanga suburbs of the city of Mutare face on a daily basis so as to propose an extension of the social security system to this informal sector. In addition, the study wishes to obtain the perceptions of employers of domestic workers on extending social security system to these workers and their role in this extension. A qualitative method was implemented with interviews carried out purposively with respect to domestic workers using snowball sampling and stratified sampling for interviews with employers. The findings show that some domestic workers ended in this type of job because their parents could not afford the fees for them to further their studies. Those with a fair level of education, findings show that they could not find a better job. The study findings reveal that domestic workers face several life challenges such as the inability to negotiate their salary, the inability for them to buy food or pay school fees for their children; the inability to save towards retirement; pregnancy - as they do not have maternity benefits; and the inability to pay for health care as well as funeral cover. Most domestic workers also fear losing their jobs as a result of occupational injuries. However, the findings also reveal that domestic workers are willing to participate in a social security insurance system on a voluntary basis and are prepared to contribute on a monthly basis. Employers of domestic workers are in favour of a social security scheme for their domestic workers. The employers were also in favour of government regulating domestic work like any other profession and were prepared to register their domestic workers if such policy was in place. Employers, however, felt domestic workers were untrustworthy, as such, they were prepared to contribute towards their social security scheme if the domestic worker stayed for at least five years under their employment. Findings also showed that employers were prepared to play a role in educating their domestic workers on the benefits of saving towards retirement. The objectives of the study were therefore realised, and it would be in the interest of the state to come up with a policy on extending social security system to the domestic workers as a way of promoting economic development and poverty reduction.
A dissertation submitted in 25% fulfilment of the requirements for a Master’s Degree in Social Security Policy Management and Administration in the Faculty of Commerce, Law and Management at the University of Witwatersrand – South Africa, February 2018
Keywords: Women--Violence against; Women and war; Family violence